Acumulação e transporte de sedimentos na microdrenagem: monitoramento e modelagem - Gomes, Ana Paula (2008)
This research aims to contribute to understanding the acumulation and distribuition´s process of sediments in the urban microdrainage, through monitoring the dry sediments in gutter of asphalted streets, sedimentologic monitoring in the outflow of microdrainage and the use of SWMM model to better understand the process involved. We collected dry samples sediments in the first square in an asphalted street situated on Marques do Herval street, in the city of Santa Maria-RS. The square has 163,26m in widht and 9m in lenght and 0,0531m/m in medium declivity. The area of microdrainage´s contribuition has 0.012km2 in which we monitorated samples collected from the storm, the flow and the concentration of sediments in suspension. In this study, we obtained 4 sedimentgrams which showed values betwen 3,48 to 6205mg/L. The study´s area was discretized in three subareas in order to apply the SWMM model. The SWMM model was used to evaluate the parameters involved in the superficial outflow and its quality in relation to the concentration of sediments in suspention. The results obtained from the calibration of parametes in relation to the superficial outflow showed a medium correlation coeficient of 0,87 and medium errors, in the peak flow and in the runoff volume of 12,45 and 5,3%, respectivaly. To simulate the quality of superficial outflow, we obtained medium correlation coeficient of 0,87 and among the observed and calculated values, we obtained medium errors of 36%. The results of the parameters of calibration were satisfactory, we have obtained a good representation of the processes involved in the microdrainage system.